#40: Next-generation Sequencing Improves the Diagnosis of Uncommon Infection in children with Hematologic Malignancies: A Case Series Study. (26th March 2021) - Zhou, Mi; Xiao, Peifang; He, Hailong; Lu, Jun; Li, Jie; Hu*, Shaoyan
Abstract: Background: Children with hematological malignancies are at high risk of infection. Various kinds of pathogens may cause infection in these patients. The effect of traditional methods on these patients is not ideal. Methods: This was a case series study. The cases of five patients with clinical symptoms of pulmonary infection. Next-generation sequencing (NGS) was used to identify pathogens in these 5 patients. Results: Uncommon pathogens were detected in five patients. Case information are shown in Table 1. Conclusion: NGS may serve as a promising tool for rapid and accurate etiological diagnosis, which could greatly improve the diagnosis of uncommon infection in children with hematologic malignancies.